2019
DOI: 10.1017/s1751731118002537
|View full text |Cite
|
Sign up to set email alerts
|

Layer pullet preferences for light colors of light-emitting diodes

Abstract: Light colors may affect poultry behaviors, well-being and performance. However, preferences of layer pullets for light colors are not fully understood. This study was conducted to investigate the pullet preferences for four light-emitting diode colors, including white, red, green and blue, in a lighting preference test system. The system contained four identical compartments each provided with a respective light color. The pullets were able to move freely between the adjacent compartments. A total of three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
10
1
1
Order By: Relevance
“…There are also initial reports of piles being initiated by attraction to shards of light within a shed ( 3 , 4 ). On a similar theme, some studies have found laying hens to have preferences for different light sources ( 15 17 ), light colors ( 18 ) and light intensities ( 19 ), with chickens spending more time in areas with their preferred light sources.…”
Section: Potential Causesmentioning
confidence: 96%
“…There are also initial reports of piles being initiated by attraction to shards of light within a shed ( 3 , 4 ). On a similar theme, some studies have found laying hens to have preferences for different light sources ( 15 17 ), light colors ( 18 ) and light intensities ( 19 ), with chickens spending more time in areas with their preferred light sources.…”
Section: Potential Causesmentioning
confidence: 96%
“…Light not only provides illumination for the poultry but also influences their physiological responses, behavior, growth and development, and production performance ( Lewis and Morris, 1998 ; Olanrewaju et al., 2006 ; Parvin et al., 2014 ; Borille et al., 2015 ). Currently, owing to the high energy efficiency, long working life, availability in different peak wavelengths, low electricity consumption, and low rearing cost ( Hassan et al., 2013 , 2014 ; Huber-Eicher et al., 2013 ; Sultana et al., 2013a , b ; Liu et al., 2017 ), light-emitting diodes ( LED ) are gradually becoming a substitute for conventional incandescent and fluorescent lights for lighting in poultry houses ( Yang et al., 2016 ; Li et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We infer that the broilers could have been sensitive to the appearance of the feed, hence the reduction in feed intake corresponding to increase of I. belina dietary inclusion levels. The reduction of feed intake due to feed appearance has been reported in similar studies (Tabeekh 2015;Radulovi c et al 2018;Li et al 2019). Also, birds using their taste can detect excessive dietary mineral and vitamins, hence resulting in refusal to consume the feed (Ferket and Gernat 2006).…”
Section: Discussionmentioning
confidence: 60%